Evaluation of 3D-CRT Treatment Planning Techniques for Breast Cancer: A Comparative Study of Collapsed Cone and Monte Carlo Algorithms Using New Quality Indices - Agid, Riyadh S.; Hassan , Fatiheea F. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
This study compares the collapsed cone (CC) and Monte Carlo (MC) algorithms for radiation treatment planning for lumpectomy of the chest wall. The aim is to evaluate how these algorithms affect dose distribution and plan quality improve treatment outcomes. Fifteen patients received left breast chest wall radiation using the 3D-conformal radiotherapy (3D-CRT) technique with CC calculation. Then plans were subsequently recalculated using the MC algorithm on the same treatment planning system. Dosimetric parameters assessed included the planning target volume (PTV), homogeneity index (HI), and conformity index. In this research, new plan quality indicators named index of achievement, index of hotness, and index of coldness were also evaluated. Organs at risks (OARs) analyzed included the ipsilateral lung, contralateral breast, heart, and spinal cord, and their data were retrieved from the dose-volume histogram (DVH) and compared among algorithms. The results indicated that both algorithms effectively covered PTV. The MC algorithm improved HI and reduced the DVH high dose to the prescribed dose. Interestingly, the CC algorithm resulted in lower mean dose to OAR, particularly the heart and ipsilateral lung, suggesting better OAR sparing. The new quality indexes, the MC algorithm demonstrated superior “index of achievement” values, indicating improved dose painting and better dose conformity within the target. In addition, the MC showed a sharper dose falloff outside the PTV, thereby improving target coverage and overall plan quality. In conclusion, the MC algorithm provides enhanced dose homogeneity and better target coverage quality, while the CC algorithm offers improved OAR protection.